The impact of inflammatory response on psychological status of medical staff during COVID-19 pandemic - Dong Wang; Haijin Li; Yansong Liu; Hong Li; Yangyang Liu; Lijun Hou (Psicologia: Reflexão e Crítica)
Abstract Background Limited research has been conducted on the relationship between inflammatory markers and psychological status in medical staff fighting COVID-19. Objective This article examines the psychological and inflammatory conditions of medical personnel working on the front lines of the battle against COVID-19. Methods: A total of 102 clinical staff members were included in this study. All subjects received the Symptom Checklist-90 questionnaire (SCL-90) and Posttraumatic Stress Disorder Checklist-Civilian questionnaires for assessing different mental symptoms. The levels of various inflammatory markers, including IL-1β, IL-2, IL-6, IL-8, TNF-a, and IFN-γ, along with GDNF, were evaluated. Results Spearman correlation analysis showed that the levels of IL-6 were positively associated with the anxiety score (Spearman’s rho = .230, p = .021), obsessive–compulsive symptoms (Spearman’s rho = .201, p = .042). The levels of IL-8 were negatively associated with the anxiety score (Spearman’s rho = -.223, p = .028), obsessive–compulsive symptoms (Spearman’s rho = -.252, p = .012), hyperarousal (Spearman’s rho = -.221, p = .028). The levels of TNF-α were positively associated with the anxiety score (Spearman’s rho = .201, p = .045), obsessive–compulsive symptoms (Spearman’s rho = .222, p = .035). Conclusion Generally, our results suggested that IL-6, IL-8 and TNF-α might play a role in the development of psychological symptoms among medical staff.